KESALAHAN GRAMATIKAL DAN PENERJEMAHAN LITERAL BUKU DURUSUN IQTISHADIYATUN MIN RAMADLAN - Ridlo Inshofa Kamil; Irhamni Irhamni; Nurul Murtadho (Fakultas Sastra Universitas Negeri Malang, 2018)
Abstrack: This study aims to describe the grammatical meaning of the translation errors and the use of literal translation in the translation procedure book Durusun Iqtishadiyatun min Ramadlan. This research is qualitative, descriptive, in accordance with the data collected in the form of words, phrases and sentences. Researchers found: (1) the translation of the meanings of grammatical errors include (a) error of morphology, which is caused by three factors, among others errors recognize form words, diction selection mistakes and errors recognize variations of word meaning, and (b) the syntax error is caused by an error in the interpretation of syntax elements in a sentence. (2) The literal translation procedure usage error in the fix uses some other procedures that; (a) transposition procedures, (b) cultural equivalence procedures, (c) the procedure modulation, (d) the procedure modulation-transposition-culture equivalence. (e) the procedure of modulation-transposition and transposition procedures (f)-modulation. permalink/DOI: dx.doi.org/10.17977/um015v46i12018p082